Tindak Tutur Ilokusi Pada Aruyo kotoba dalam Manga Ranma 1/2 - Az-Zahra Callista Phramesti; Pika Yestia Ginanjar (Universitas Diponegoro, 2024)
The Japanese language used in fictional work differs from the standard Japanese language. This language variety, which highlights the stereotypical qualities of a character, is called yakuwarigo or role language. Among the many types of role language, aruyo kotoba highlights the characteristics of a Japanese-speaking Chinese character. This study aims to describe the types and meaning of illocutionary act on aruyo kotoba utterances using the pragmatic theory. The source of the data is a manga titled Ranma 1/2 by Takahashi Rumiko which was first published in 1987. The research is conducted using note-see method for the data collection. Then, the theory of Koizumi (1993) is used to classify the data according to its illocutionary speech act types based on the context of the utterances. The result shows that there are 27 data of illocutionary act on aruyo kotoba in the manga of Ranma 1/2 with the aru and yoroshi ending in sentences, namely 4 data of assertive illocutionary act, 7 data of expressive illocutionary act, 2 data of comissive illocutionary act, and 14 data of directive illocutionary act. The meaning contained in the illocutionary acts are tell, emphasize, insult, complain, getting mad, compliment, insinuate, command, and request. <a href=